THE INFLUENCE OF EDUCATION ABOUT STUNTING ON MOTHER'S KNOWLEDGE - Eka, Eka Hadrayani; Fadhilah Gani, Nurul; Risnawati; Muthahharah (Universitas Islam Negeri Alauddin Makassar, 2023)
Stunting is a chronic malnutrition problem caused by a lack of nutritional intake in children over a long period which can result in growth disorders in children. Education can increase parents' knowledge and attitudes in providing children with nutrition so that it can become an alternative intervention to improve health behavior in dealing with stunting. In the research area, there are 71 stunted children. This research aims to determine the effect of education about stunting on mothers' knowledge in Pallantikang village, Jeneponto Regency. This research is quantitative research using a quasi-experimental method with a one-group pre-post test design approach and using the Wilcoxon test. In this research design, before the intervention is given, a pre-test is first given which aims to assess the mother's knowledge about stunting. After the intervention is given, a post-test will be given. The intervention that will be carried out in this research is education about stunting using lecture methods and poster media. The results of the research show the p-value = 0.000 and the median pre-test is 9.00 while the post-test value is 13.00. From the results of the research conducted, it can be concluded that there is an influence of education about stunting on the knowledge of mothers in Pallantikang Village, Jeneponto district, before and after being given education about stunting. Future research needs to examine further the behavior of mothers in providing nutrition for toddlers after receiving nutrition education. Providing health education through poster media can increase knowledge and can be a good health education technique for the community.